2020
DOI: 10.1002/jccs.202000006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical exploration on single crystal, structural, and quantum chemical parameters of (E)‐7‐(arylidene)‐1,2,6,7‐tetrahydro‐8H‐indeno[5,4‐b]furan‐8‐one derivatives: A comparative study

Abstract: In the present research work, biologically important halogen-substituted (E)-7-(arylidene)-1,2,6,7-tetrahydro-8H-indeno[5,4-b]furan-8-one derivatives are studied from a structural investigation point of view. For a detailed molecular structure description, some quantum-chemical calculations were performed by using the density functional theory method with a basis set 6-311++G(d,p). The optimized molecular geometry, bond length, atomic charges, bond angle, and harmonic vibrational frequencies have been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…55 B3LYP/6-311G(d,p) is taken into consideration for these purposesin the present discussion.The information about bond lengths is very crucial to get insights into inter and intra molecular interactions, hydrogen bonding effects and also chemical reactivity patterns. [56][57][58] For the title compound, the bonds C5-N35 and C8-N33 are having 1.4157 Å and 1.3979 Å respectively. This will makenitrogen atom of C5-N35 bond better nucleophile since the bonding electrons are more polarized due to longer bond length.When acidic nature of H34 and H36 is compared, it is observed that H36possessmore acidic strength which is supported by their bond lengths and Mulliken atomic charge values.…”
Section: Geometrical Parametersmentioning
confidence: 99%
“…55 B3LYP/6-311G(d,p) is taken into consideration for these purposesin the present discussion.The information about bond lengths is very crucial to get insights into inter and intra molecular interactions, hydrogen bonding effects and also chemical reactivity patterns. [56][57][58] For the title compound, the bonds C5-N35 and C8-N33 are having 1.4157 Å and 1.3979 Å respectively. This will makenitrogen atom of C5-N35 bond better nucleophile since the bonding electrons are more polarized due to longer bond length.When acidic nature of H34 and H36 is compared, it is observed that H36possessmore acidic strength which is supported by their bond lengths and Mulliken atomic charge values.…”
Section: Geometrical Parametersmentioning
confidence: 99%
“…B3LYP stands for "Becke, 3-parameter, Lee-Yang-Parr". The structural and chemical properties of organic molecules have been effectively explored using the density functional theory based on theoretical quantum calculations [38][39][40][41][42]. As theoretical calculations are compared to experimental findings, a lot of knowledge is gained.…”
Section: Introductionmentioning
confidence: 99%
“…Some instrumental examples of the DFT applications are vibrational assignments, Raman spectrum analysis, NMR study, mechanistic studies, and quantum chemical exploration. [32][33][34][35][36][37][38][39][40][41] By considering these vital aspects and in continuation of our work for the synthesis of antimicrobials, we are eager to report the computational studies along with valuable insights into antifungal and antioxidant studies of the titled compound. The various structural, spectroscopic and quantum chemical facets have been explored to study the structural and chemical nature of the FMBIF molecule.…”
Section: Introductionmentioning
confidence: 99%